Inter-model comparison of embedded-tube radiant floor models in BPS tools. Issue 2 (3rd March 2016) - Brideau, S.A.; Beausoleil-Morrison, I.; Kummert, M.; Wills, A.
Abstract : Hydronic radiant floor heating and cooling can potentially reduce energy consumption in buildings. Numerous building performance simulation (BPS) tools contain models for predicting the heat transfer between embedded-tube radiant floor systems and building thermal zones. However, the accuracy, limitations, and methodologies of these models, and their implementations into BPS tools, have never been contrasted in the literature. This paper describes the approaches employed by TRNSYS, ESP-r, and EnergyPlus for modelling embedded-tube radiant floors. An inter-model comparison is then presented for test cases designed to explore model performance. The predictions from the three BPS tools are compared to each other as well as to predictions made with a transient stand-alone finite element analysis tool. Significant issues are identified with the embedded-tube radiant floor models in all three BPS tools.